Showing the flag in sober Dutch style: Post-war embassy buildings in Washington and Bonn (Bulletin KNOB, 2019)
In 1964 the Netherlands inaugurated two new embassy buildings: in Washington DC, designed by the Dutch architect Piet Tauber, and in Bonn, designed by the German architect Ernst van Dorp. During the opening of both buildings, the Dutch dignitaries, who included the respective ambassadors, stressed that the new embassies, while solving existing accommodation problems, were also a symbolic gesture. Embassies, which housed the Netherlands’ foreign diplomatic missions, were political, representative buildings and as such carried symbolic connotations.This article relates to part of a doctoral study focusing on the representational role of Dutch embassy buildings from the Second World War to the present day and their all-important symbolism. Archival research was conducted into the history of the origins and reception of two Dutch embassy buildings from the same post-war reconstruction period when the first embassy buildings specifically commissioned by the Dutch government were constructed. The embassies in Washington DC (1960-1964) and Bonn (1962-1964), realized in quick succession, were of comparable political importance and were distinguished by the use of brick, a material often associated with the Netherlands. In addition to the choice of materials, the sober design of both buildings was seen as stereotypical of the national character. Given the representative function of the embassies, which housed the two biggest and most important Dutch diplomatic missions, the relation between political, national identity and architecture seems to have played a role in the realization of both buildings.In both Washington and Bonn the Dutch government purchased a plot in a residential area, at a suitable distance from the seat of government. Both designers explicitly took account of the surroundings and opted for an architecture that was modern yet understated. Piet Tauber (1927-2017), for whom this accorded with his own design principles, sought to balance functionality, context and architectural expression, resulting in ‘simplicity and honesty’. Ernst van Dorp (1920-2003) emphasized the specific function of an embassy building. As the symbol of a nation in a foreign country, the design ought to conform to the national character and the context, without drawing undue attention to itself. As well as having an ‘affinity’ with the country being represented, the building should be ‘durable’ and age gracefully. According to the German architect brick and glass were more durable and revealed more ‘character’ as they aged. Both approaches resulted in a highly contextual building that was widely regarded as representative of the home country in the choice of material, sober architectural appearance, and taut, functional design. Although the VIPs at the openings in 1964 referred to the symbolism of the buildings, there is no indication in the archival material that the national significance of the buildings was actually specified in the design commission. Neither style nor material was stipulated. Rather, the embassies in Washington and Bonn demonstrate how a balance was sought with the context of the host country. To what extent this was a deliberate political strategy that was also applied to later Dutch embassy buildings and hence typically Dutch, is a subject for further research.